Prevalência de mycobacterium bovis e estudo dos fatores associados entre casos de tuberculose atendidos em centros de referência, Brasil, Março 2008 Fevereiro 2010 - Marcio Roberto Silva (2011)
Introduction: Mycobacterium bovis is an organism of the M. tuberculosis complex that causes animal tuberculosis, but can also affect human beings. The relative contribution of Mycobacterium bovis to the global tuberculosis (TB) is likely to be underestimated due to its dysgonic and slow growth characteristics and because of the absence of pyruvate in most used media is unfavorable for its primary isolation. In Brazil Mycobacterium tuberculosis complex (MTC) cultures, identification and susceptibility tests are performed only in tuberculosis (TB) referral centers, generally for particular cases. Furthermore, solid, egg-based, glycerol-containing (without pyruvate supplementation) Löwenstein-Jensen (LJ) or Ogawa media are routinely used, unfavouring M. bovis isolation. The main objectives of this thesis were: 1) To describe the identification of Mycobacterium tuberculosis complex based on amplification and sequencing of oxyR pseudogene from stored Ziehl-Neelsen-stained sputum smears obtained from patients with pulmonary tuberculosis diagnosed at two public referral laboratories from Juiz de Fora, Minas Gerais State, in 2007 (original article 1); 2) To determine the relative importance of M. bovis to the global tuberculosis in suspected TB referred to the two health centers from Juiz de Fora, Minas Gerais State, from March 2008 to February 2010 (original article 2); 3) To evaluate factors associated with human infections due to M. bovis and atypical mycobacteria (original article 3). The methods for achieving such goals and the results were presented as three original articles and will be summarized respectively. Original article 1: A cross-sectional analysis of stored Ziehl-Neelsen (ZN)-stained sputum smear slides (SSS) obtained from two public tuberculosis referral laboratories located in Juiz de Fora, Minas Gerais, was carried out in order to distinguish Mycobacterium bovis from other members of MTC. A two-step approach was used, (a) oxyR pseudogene amplification to detect MTC; and, subsequently, (b) an allele-specific sequencing based on the polymorphism at position 285 of this gene for distinguishing Mycobacterium bovis from other members of MTC. OxyR pseudogene was successfully amplified in 100 (56.5%) among 177 SSS available from 99 individuals. No molecular profile of M. bovis was found. The multivariate analysis indicated that AFB results and source laboratory were associated (p<0.05) with oxyR pseudogene amplification. AFB++ sputum smears showed more oxyR pseudogene amplification than those with AFB0, possibly due to the amount of DNA. One of the two source laboratories presented a greater chance of oxyR pseudogene amplification, suggesting that differences in sputum conservation between laboratories could have influenced the preservation status of DNA. This study provides evidence that stored-ZN-stained sputum smears can be used for molecular detection of MTC and does not provide evidence of M. bovis being associated with human pulmonary tuberculosis in an urban area of Minas Gerais. Original article 2: A cross-sectional analysis was carried out to determine the relative importance of M. bovis as a public health threat in Juiz de Fora, Minas Gerais. We investigated 1000 specimens (603 suspected TB patients) inoculating their clinical samples onto routine LJ and Stonebrink (SB) pyruvate enriched media. A total of 356 specimens were culture positive for Mycobacterium spp. either in LJ or SB medium and 178 TB cases had the implied micobacteria defined by conventional and/or molecular speciation methods. Among the 178 TB cases, we detect one single M. bovis by conventional methods. But, this case couldnt be confirmed by molecular speciation methods. This sample didnt present either gen pncA or pseudogene oxyR amplifications. Also, supposed DNA present on 38 formalin fixed and paraffin wax embedded biopsy tissue samples from 38 TB patients were oxyR genotyped and 14 were confirmed as TB. Two of them were recognized as M. bovis cases. Our data indicate that M. bovis importance on the burden of human TB in Juiz de Fora, Minas Gerais, Brazil, was low. Three (1,5%) were recognized as M. bovis-M. tuberculosis co-infections out 191 confirmed patients for Mycobacterium spp. infections. Additionally, M. tuberculosis was detected alone in 184 (96.4%) of 191 patients (95% CI = 93.6% - 98.9%), and M. avium-intracellulare evidences alone or in co-infection with M. tuberculosis was found in 4 (2.0%) of 191 patients (95% CI = 0 - 4.1%). Original article 3: We evaluated possible factors associated respectively to M. bovis co-infections (study 1) and M. avium-intracellulare evidences (study 2) by means of two case-control studies nested in a cross-sectional study. In this study mycobacteria involved in 191 patients were defined by conventional and/or molecular speciation methods. We selected 15 controls (TB due to M. tuberculosis) for each M. bovis co-infection or M. avium-intracellulare evidence, respectively. In both studies, controls were matched by age group (cutoff point 38 years) and sex (Study 1) and by age group (cutoff point 38 years), sex and type of entry into service (study 2). In Study 1, M. bovis co-infections were associated (p 0.05) with both a zoonotic exposure (OR=16,85; IC 95% = 0,64-275,18) and the clinical form of TB (OR = 16.00, 95% CI = 1.21 to 209.94). In Study 2, M. avium-intracellulare evidences presented an association (p 0.05) with HIV / AIDS (OR = 13.36, 95% CI = 1.26 to 140.93).